A protocol to evaluate the impact of embedding Public and Patient Involvement in a structured PhD program for stroke care - Horgan, Frances; Lennon, Olive; Hickey, Anne; Sorensen, Jan; Kroll, Thilo; McCartan, Deirdre; Hall, Patricia; O'Callaghan, Geraldine; Fitzgerald, Clare; Hickey, Julianne; Fahy, Martin; Osborne, Philip; et al. (Frontiers in Rehabilitation Sciences, 2022)
Background Embedding Public and Patient Involvement (PPI) in postgraduate research has been recognised as an important component of post-graduate training, providing research scholars with an awareness and a skillset in this area which prepares them for future roles as independent, collaborative researchers. Improving Pathways for Acute STroke And Rehabilitation (iPASTAR) is a structured PhD training programme (Collaborative Doctoral Award (CDA)) which aims to design a person-centred stroke pathway throughout the trajectory of stroke care, to optimise post-stroke health and wellbeing. PPI is embedded at all stages. Purpose The iPASTAR research programme was strongly informed by a round-table PPI consultation process with individuals who experienced stroke and who provided broad representation across ages, gender, geographical locations (urban and rural) and the PhD themed areas of acute care, early supported discharge and lifestyle-based interventions after stroke. Four PhD scholars taking part in the CDA-iPASTAR now work collaboratively with four stroke champions, supported by a wider PPI advisory panel, presenting an opportunity for experiential PPI training. Methods The proposed study aims to evaluate the process and impact of embedding PPI during a PhD programme. We will conduct a longitudinal mixed-methods evaluation, over 24-months and explore the experiences of the key stakeholders involved. The participants will include PhD scholars, PPI partners (PPI Advisory Group and PPI Champions), PhD supervisors and a PPI manager. An independent researcher will conduct the evaluation. We will include focus groups, individual interviews and participant reflections. Qualitative data will be analysed using thematic and content analysis, quantitative data will be analysed using descriptive statistics. Discussion PPI and patient voice initiatives bring together researchers, family, and people with health care issues into meaningful dialogue and allow the development of a patient-voice learning network. Embedding PPI training within a PhD programme is a novel approach to building meaningful capacity in PPI partnerships in stoke research.